Atomic habits An easy and proven way to build good habits & break bad ones - Clear, James (New York : Penguin Random house, 2018)
Atomic Habits is a self-improvement book that explores the power of small, consistent changes in shaping habits and achieving long-term success. James Clear presents a practical, science-based approach to habit formation, emphasizing how minor adjustments can lead to remarkable results over time.
Keywords: Psychology-self help